MIGA Annual Report 2011 : Insuring Investments, Ensuring Opportunities - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2012)
The report highlights Multilateral Investment Guarantee Agency's (MIGA's) innovation, flexibility, and ability to deliver on its own modernization agenda. This year, the agency secured significant amendments to its Convention that enhances its value as a multilateral provider of political risk insurance. These amendments, approved by the Council of Governors in August, have already enabled MIGA to support projects that would not previously have been possible. In fiscal year 2011, MIGA provided $2.1 billion in new guarantee coverage a record high for the agency, and a 43 percent increase over the previous year, which indicates renewed interest in political risk-mitigation products. MIGA has shown renewed diversification and regional outreach from its support for a manufacturing plant in Iraq, to an agribusiness venture in Liberia, to a mining feasibility study in Indonesia, and to banking endeavors supporting small and medium enterprises in 14 countries. MIGA's concerted efforts to encourage foreign direct investment (FDI) into the Middle East and North Africa region have been especially important this year. This report also notes important amendments to MIGA's convention, approved by the Council of Governors, which took effect in November 2010. These historic amendments greatly enhance our ability to support clients. Now MIGA able to cover stand-alone debt and some existing investments, putting us in a better position to support investors in times of uncertainty. Clients have responded very positively to MIGA's expanded authority, which has also contributed to this year's increased business volume.